Enhanced polarization from flexible hierarchical MnO2 arrays on cotton cloth with excellent microwave absorption. Issue 28 (5th July 2019) - Li, Xiao; Wang, Lei; You, Wenbin; Xing, Linshen; Yang, Liting; Yu, Xuefeng; Zhang, Jie; Li, Yuesheng; Che, Renchao
Abstract : Well-designed CC@MnO2 (α phase instead of δ phase) exhibits the best absorption performance (−53.2 dB). Abstract : To develop flexible microwave absorbers with strong attenuation capability has become a formidable challenge for applications of camouflage, stealth, and anti-electromagnetic pollution. Herein, a series of highly uniform cotton cloth@MnO2 (CC@MnO2 ) hierarchical structures with superior absorption performances were fabricated by simultaneously changing their intrinsic (α/δ phase) and extrinsic (2D/1D geometry) characteristics. The distinct absorption capability was dominantly contributed by the vertically grown dielectric MnO2 1D nanotube and conductive CC substrate, which could serve as a highly oriented backbone to ensure rapid electron transportation. Therefore, a well-designed CC@MnO2 sample (α phase instead of the δ phase) exhibits the best absorption performance. The maximum reflection loss (RL) is −53.2 dB at 5.4 GHz and the effective bandwidth is 5.84 GHz for a thickness of only 2 mm. This unique structure exhibits polarization, conduction loss, and strong dissipation capability, which can be attributed to the high density of accumulated charges trapped at the interface, as confirmed by the electron holography analysis. Meanwhile, the MnO2 coating does not affect the original flexibility of the CC and yields a massive interface and electronic conduction path. It is expected that CC@MnO2 might shed a new light on the design of microwave absorbers.